Association of traditional risk factors with coronary artery disease in nonagenarians: the primary role of hypertension - Yayan J (Dove Medical Press, 2014)
Josef YayanDepartment of Internal Medicine, Division of Pulmonary, Allergy and Sleep Medicine, Saarland University Medical Center, Homburg, Saarland, GermanyBackground: Previous studies have shown different relationships between traditional cardiovascular risk factors for coronary artery disease (CAD) in very elderly people. Although new associations with CAD have been reported, there is also evidence of the possibility of new therapeutic strategies for the treatment or prevention of CAD. Design: This article retrospectively examines the possible association of traditional cardiovascular risk factors with CAD in very elderly people aged >90 years. This study represents the hypothesis that the elderly aged >90 years have a different cardiovascular profile with respect to CAD than patients <90 years old. Methods: Data on all patients aged >90 years who received a cardiac catheterization were collected from hospital charts from the Department of Internal Medicine, Saarland University Medical Center, Germany, within the study period of 2004–2013. The cardiovascular risk profiles were compared in patients aged >90 years with and without CAD after cardiac catheterization. Results: One hundred and six out of 67,976 (0.2%, mean age 91.6±1.8 years, 40 female [37.7%]; 95% confidence interval [CI]: 0.1–0.2), and out of a total of 114 of the very elderly patients, were found to have CAD. From the results of this study, the author could establish only a causal relationship between hypertension and CAD in very elderly people (P=0.005). At best, this is just an association with a higher risk of CAD in this age group. Several studies with similar outcomes are needed to establish causality. Conclusion: This study could find no link between CAD and traditional risk factors, except for hypertension.Keywords: aging, hypertension, diabetes, hypercholesterolemia, hyperlipidemia, obesity